Family-Based Intervention Program for Adolescents Vulnerable to Drug Abuse in Dukong Village, Belitung Regency - Dianti E. Kusumawardhani; Nina Kreasih (Jurnal Indonesia Sosial Teknologi, 2024)
This study adopted a family-based intervention model (Family United) developed by BNN and UNODC. The participants in this study were 8 (eight) vulnerable adolescents aged 14-18 years along with their families who live in Dukong Village. The intervention was carried out for 4 (four) sessions over 4 (four) days. The instruments used were the AntiDrugs Scale, Family Assessment Device and behavioural checklist to measure changes in family communication behaviour and adolescent behaviour to refuse drugs. Family communication behaviour after 4 (four) weeks after the intervention decreased than immediately after the intervention, while adolescents' behaviour to refuse drugs tended to remain. T-test results showed anti-drug scale scores (p<0.001) after and before the intervention was given. Meanwhile, the results of the posttest and pretest of family functioning showed (p<0.001) from the parents' side and the adolescents' side.